Screening of genes encoding adhesion factors and biofilm production in methicillin resistant strains of Staphylococcus aureus isolated from Palestinian patients - Kifaya Azmi; Walaa Qrei; Ziad Abdeen (BMC Genomics, 2019)
Abstract Background Intercellular adhesion and biofilm production by Staphylococcus aureus makes these bacteria resistant to antimicrobial therapy. Here, Methicillin-resistant Staphylococcus aureus (MRSA) strains were characterized and the prevalence of genes encoding adhesion factors and biofilm formation was determined. Results All 248 MRSA isolates identified by cefoxitin disc diffusion were positive for the mecA gene. SCCmec-IV was the most frequently detected genotype (92.7%) and SCCmec-IVa was also very prevalent (84.3%). The quantitative microtiter plate assay showed that all the isolates were able to produce biofilm with levels ranging from high (21%) to moderate (46.4%) to low (32.7%). All the strains possessed the icaD/icaA genes and produced biofilm (P < 0.05). None of the isolates possessed the bap gene. Furthermore, 94.8% of the isolates were positive for eno, 80.2% for clfA and for clfB, 78.2% for fnbA, 76.2% for ebps, 62.2% for fib, 39.9% for cna and 29.0% for fnbB. Also, nearly 69.8% of the isolates were positive for the gene sarA. All four agr groups were present: agr group 1 was predominant with 39.5%; agr group 3. agr group 2 and 3 strains carried more toxin-producing genes, and frequently produced more toxin. Sixty-six (26.6%) of the strains were multidrug resistant. All were vancomycin sensitive. Agr group I is more resistant to ciprofloxacin and gentamicin while agr group III is more resistant to erythromycin. Maximum sensitivity was to gentamicin and SXT, and they could be considered drugs of choice for controlling MRSA mediated infections in this region. Conclusions Biofilm development in MRSA might be an ica dependent and one needs to investigate the involvement of other global regulators, agr and sarA, and their contribution to the biofilm phenotype, as the high rate of biofilm production among the studied strains of S. aureus.